Long QT Syndrome KCNH2 Variant Induces hERG1a/1b Subunit Imbalance in Patient-Specific Induced Pluripotent Stem Cell–Derived Cardiomyocytes. (April 2021) - Feng, Li; Zhang, Jianhua; Lee, ChangHwan; Kim, Gina; Liu, Fang; Petersen, Andrew J.; Lim, Evi; Anderson, Corey L.; Orland, Kate M.; Robertson, Gail A.; Eckhardt, Lee L.; January, Craig T.; et al.
Abstract : Background: Inherited long QT syndrome type 2 results from variants in the KCNH2 gene encoding the human Ether-à-go-go related gene 1 (hERG1) potassium channel. Two main isoforms, hERG1a and hERG1b, assemble to form tetrameric channel. The N-terminal PAS (Per/Arnt/Sim) domain, present only on hERG1a subunits, is a hotspot for pathogenic variants, but it is unknown whether PAS domain variants impact hERG1b expression to contribute to the long QT syndrome type 2 phenotype. We aimed to use patient-specific induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) to investigate the pathogenesis of the hERG1a PAS domain variant hERG1-H70R. Methods: Human iPSCs were derived from a patient with long QT syndrome type 2 carrying the PAS domain variant hERG1-H70R. CRISPR/Cas9 gene editing produced isogenic control iPSC lines. Differentiated iPSC-CMs were evaluated for their electrophysiology, hERG1a/1b mRNA expression, and hERG1a/1b protein expression. Results: Action potentials from single hERG1-H70R iPSC-CMs were prolonged relative to controls, and voltage clamp studies showed an underlying decrease in IKr with accelerated deactivation. In hERG1-H70R iPSC-CMs, transcription of hERG1a and hERG1b mRNA was unchanged compared with controls based on nascent nuclear transcript analysis, but hERG1b mRNA was significantly increased as was the ratio of hERG1b / hERG1a in mRNA complexes, suggesting posttranscriptional changes. Expression of complex glycosylated hERG1a in hERG1-H70R iPSC-CMs was reduced due to impaired protein trafficking, whereas the expression of the complex glycosylated form of hERG1b was unchanged. Conclusions: Patient-specific hERG1-H70R iPSC-CMs reveal a newly appreciated mechanism of pathogenesis of the long QT syndrome type 2 phenotype due to both impaired trafficking of hERG1a and maintained expression of hERG1b that produces subunit imbalance and reduced IKr with accelerated deactivation. Graphic Abstract: A graphic abstract is available for this article. Abstract : Supplemental Digital Content is available in the text.